Correlation of reduced amniotic fluid index with neonatal outcome - Chaudhary, Rachna; Dhama, Vandana; Singh, Shakun; Singh, Madhumita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Amniotic fluid assessment is an essential part of evaluation of fetus health in terms of fetal distress, meconium aspiration, IUGR, Non-reassuring fetal heart rate patterns, birth asphyxia, low birth weight, low Apgar-scores and NICU Admissions. Methods: This prospective observational study included 200 antenatal patients of term gestation of which 100 cases with AFI<8 and 100 controls with AFI ≥8 but ≤ 15 were included in study. Ultrasonography and NST were done and results of both groups compared for the presence of meconium passage, non-reactive NST, birth asphyxia, low Apgar-scores, low birth weight, NICU admissions and neonatal deaths. Results: There was increased incidence of non-reactive NST (40% vs 12%), meconium stained (33% vs 10%) in oligohydramnios group. In cases 49% of patients had vaginal delivery while in controls 78%. 51% underwent LSCS in cases while in controls 22%. Apgar score <7 was found in 7% vs 4%. Birth weight was <2.5 kg in 35% vs 13%. NICU admissions in study group was 15% vs 11%. The neonatal death was similar in both cases groups. Conclusions: Oligohydramnios affect the neonatal outcome in terms of meconium stained liquor, non-reassuring fetal heart rate, low birth weight, birth asphyxia, low Apgar-scores and NICU Admissions and neonatal death but the difference was not statistically significant. Early detection of oligohydramnios and its management may help in reduction of perinatal morbidity and decreased caesarean deliveries.